Արքայի կամ աստվածամարդու ինքնության նշանները Լևոն Խեչոյանի «Արշակ արքա, Դրաստամատ Ներքինի» վեպում - Ավետիսյան, Սաթենիկ (Արմավ հրատ.)
The words «king» and «melik» are synonyms, meaning those descended from the God Ar or those who keep the divine laws «me» on Earth (Melikutyun).In his novel «Arshak king, Drastamat eunuch», Levon Khechoyan considers the substantiation of Arshak II to be a godman to be an ideologically important issue.For this purpose he uses the image of the Aryan symbol goat, Arshak fights with the bull, defeats him as a goat, which, according to the ancient Sumerian-Akkadian mythology, symbolizes the victory of the sacred animal of the аrmenian GodHa:a, the goat over the bull, the sacred animal of the God of Moon An and becomes evidence of the divine origin of King Arshak. Слова „царь» и „мелик» являются синонимами, означающими потомков Бога Ар или тех, кто соблюдает божественные законы„ме»на Земле (Меликутюн).В романе „Царь Аршак, евнух Драстамат» Левон Хечоян считает идеологически важным вопросом обоснование того, что Аршак II является божьим человеком.Для этого он использует образ арийского символа козла, Аршак сражается с быком, побеждает его как козел,что, согласно древней шумеро-аккадской мифологии и клинописи, символизирует победу священного животного армянского бог Эя, козла над быком, священным животным бога Луны Ан, и становится свидетельством божественного происхождения царя Аршака.
Keywords: Գրականագիտություն